The fixed nodal position method for form finding of high-precision lightweight truss structures. (April 2019) - Yuan, S.; Yang, B.
Abstract: A new form-finding method, namely the Fixed Nodal Position Method (FNPM), is developed for design of geometric configuration and internal force distribution for a class of truss structures with a requirement of high shape or surface accuracy. Different from existing form-finding methods, which usually follow a stress-first-and-displacement-later procedure, the FNPM first assigns nodal coordinates for a truss structure, and then determines the internal force distribution of the structure by an optimization process. The highlight of the FNPM is that the prescribed nodal coordinates are unchanged during the form finding process. This special feature of fixed nodal positions allows the proposed method to place the nodes of a truss structure at desired locations, satisfying complicated constrains and yielding high shape/surface accuracy as required. Moreover, because the assignment of geometric configuration (nodal coordinates) and the determination of internal force distribution are undertaken separately, the computational effort in the FNPM-based form finding is much less than that by a conventional method. The proposed method is applied to two large deployable mesh reflectors of 217 nodes and 865 nodes, respectively, and show high efficiency and accuracy in form finding.